2017
DOI: 10.1128/jvi.00785-17
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Escapes NK Cell Detection by Upregulating Major Histocompatibility Complex Class I Molecules

Abstract: NK cells are innate lymphocytes that participate in many immune processes encompassing cancer, bacterial and fungal infection, autoimmunity, and even pregnancy and that specialize in antiviral defense. NK cells express inhibitory and activating receptors and kill their targets when activating signals overpower inhibitory signals. The NK cell inhibitory receptors include a uniquely diverse array of proteins named killer cell immunoglobulin-like receptors (KIRs), the CD94 family, and the leukocyte immunoglobulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 70 publications
4
47
1
3
Order By: Relevance
“…In our system, CXCL14 restoration of MHC-I expression must overcome the activity of both HPV oncoproteins that have been shown to suppress MHC-I surface expression through multiple mechanisms. Finally, in support of modest changes of MHC-I enacting protection against CD8 + T-cell killing, a recent publication has reported that Zika virus upregulates MHC-I expression to protect the cell from NK-cell killing [42]. Although the shifts in MHC-I were modest, it was sufficient to enact protection from NK-cell killings.…”
Section: Discussionmentioning
confidence: 96%
“…In our system, CXCL14 restoration of MHC-I expression must overcome the activity of both HPV oncoproteins that have been shown to suppress MHC-I surface expression through multiple mechanisms. Finally, in support of modest changes of MHC-I enacting protection against CD8 + T-cell killing, a recent publication has reported that Zika virus upregulates MHC-I expression to protect the cell from NK-cell killing [42]. Although the shifts in MHC-I were modest, it was sufficient to enact protection from NK-cell killings.…”
Section: Discussionmentioning
confidence: 96%
“…(84, 86) Other mechanisms of flavivirus innate immune antagonism include induction of major histocompatibility expression (MHC-I) on the surface of infected cells to evade natural killer cell-mediated lysis. (89, 90) The viral NS1 protein can also dysregulate the humoral complement system, thus allowing the virus to evade both direct destruction and destruction of infected cells. (91, 92) Thus, flaviviruses excel at evading the innate immune response by preventing host cell recognition of viral pathogen-associated molecular patterns and inhibiting antiviral signaling pathways.…”
Section: How Zikv Escapes the Immune Response And Emerging Viruses Wimentioning
confidence: 99%
“…). However, expression of NK receptors is suppressed in HIV patients, which dampen NK response and infections, and Zika virus up‐regulated MHC I molecules to escape NK cell detection . It was reported at the meeting that herpes viruses evade NK cell killing through down‐regulating NKG2D ligands by HHV‐6A proteins U20 and U21 (Abstract 75).…”
Section: Nk Receptors and Functionsmentioning
confidence: 99%
“…However, expression of NK receptors is suppressed in HIV patients, which dampen NK response and infections, 40,43 and Zika virus up-regulated MHC I molecules to escape NK cell detection. 44 45 TRAIL is a cell-death inducing ligand and plays a role in the antimetastatic and antiviral functions of NK cells and in the regulatory function of NK cells in eliminating virus-specific T cells during chronic inflammation. New findings showed that NKp46 is an intrinsic regulator of TRAIL protein expression in liver resident type 1 innate lymphoid cells (Abstract 17).…”
Section: Nk Cell Receptors and Their Ligands In Microbial Host Defensementioning
confidence: 99%